2019
DOI: 10.1016/j.foodres.2018.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds characterization by LC-DAD- ESI/MSn and bioactive properties of Thymus algeriensis Boiss. & Reut. and Ephedra alata Decne

Abstract: Scientific research has been focused on finding natural occurring molecules from plant origin. Herein, infusion, decoction and hydroethanolic extracts of Thymus algeriensis Boiss. & Reut. and Ephedra alata Decne. from Algeria were phytochemically characterized by LC-DAD-ESI-MSn, and evaluated regarding bioactive properties (antioxidant and antibacterial). Flavonol and flavone glycoside derivatives and phenolic acids, specially rosmarinic acid and kaempferol-O-glucuronide were the major compounds in T. algerien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 35 publications
5
85
0
1
Order By: Relevance
“…Plants from the genus Thymus is used traditionally as herbal teas, culinary spices, condiments, and as analgesic, anti-rheumatic, antiseptic, astringent, and diuretic agents. Additionally, the plants are considered an important source of essential oils and the thyme oil, with its diverse biological properties including antioxidant, antibacterial, antimycotic, and age-delaying properties, is included in the world's top ten essential oils [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants from the genus Thymus is used traditionally as herbal teas, culinary spices, condiments, and as analgesic, anti-rheumatic, antiseptic, astringent, and diuretic agents. Additionally, the plants are considered an important source of essential oils and the thyme oil, with its diverse biological properties including antioxidant, antibacterial, antimycotic, and age-delaying properties, is included in the world's top ten essential oils [3].…”
Section: Introductionmentioning
confidence: 99%
“…The herbaceous fragrant, Thymus algeriensis, is an endemic plant to Libya, Tunisia, Algeria, and Morocco and considered as the most widespread North African species. The plant is largely used as a culinary herb and as a traditional medicine to treat digestive and respiratory infections (e.g., gastrointestinal dysentery, colds), prostate adenoma, and to prohibit abortion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hot water extract of T. vulgaris leaf showed dose‐dependent DPPH‐scavenging capability and it was similar to standard antioxidants butylhydroxyanisol (BHA) and butylated hydroxytoluene (BHT) at a dosage of 1.5 mg mL −1 . Phenolic acids and flavonoid derivatives also showed correlations with the antioxidant activity . As the main compound in the methanol extract of T. dacicus , rosmarinic acid ( 71 ), which reached up to 71.33±1.11 mg g −1 , possessed more remarkable antioxidant activity (FRAP values=16.54±0.38 m m Fe 2+ g −1 ) than that of both methanol extract and ascorbic acid …”
Section: Biological Activitiesmentioning
confidence: 86%
“…[88] Phenolic acids and flavonoid derivatives also showed correlations with the antioxidant activity. [108] As the main compound in the methanol extract of T. dacicus, rosmarinic acid (71), which reached up to 71.33 � 1.11 mg g À 1 , possessed more remarkable antioxidant activity (FRAP values = 16.54 � 0.38 mM Fe 2 + g À 1 ) than that of both methanol extract and ascorbic acid. [104] T. quinquecostatus CLEAK extracts could protect Chang liver cells from oxidative damage induced by tert-butylhydroperoxide (t-BHP) through their ability to enhance the cell viability, mediate production of ROS and mitochondria function associated with cell apoptosis including membrane potential loss.…”
Section: In Vitromentioning
confidence: 97%
“…One of the probable reasons for it is the higher content of polyphenolic and avonoid compounds in methanol fraction of Ephedra alata. In fact, Ziani et al [27] have reported that The hydro-methanol crude extract contained the maximum number of phenolic Obesity has been proven to lead to many complications including cardiovascular diseases, chronic kidney failure, foot ulcers, and type 2 diabetes. Diabetes one of the most challenging chronic disorder of the 21st century that alters carbohydrate, protein, and fat metabolisms.…”
Section: Discussionmentioning
confidence: 99%